Preferences for processed tomato products’ attributes: an explorative analysis of Italian consumers using a large sample - Cammarelle, Antonella; Bimbo, Francesco; De Devitiis, Biagia; Latino, Maria Elena; Corallo, Angelo; Viscecchia, Rosaria (Frontiers in Sustainable Food Systems, 2024)
Introduction Price competition in the tomato market may lead Italian processing companies to adopt product differentiation strategies to attract consumers and raise revenues. Exploring consumers’ preferences for processed tomato products’ attributes can support companies in implementing product differentiation strategies and succeed in the market. Methods This study used a convenience sample of 602 Italian consumers to identify consumers’ preferences for processed tomato products’ attributes selected through a literature review and tested by the Best Worst Scaling (BWS) method. Also, a two-step cluster analysis was used to identify and size consumer groups with common preferences for tested product’s attributes. Results Overall, our results showed that Italian consumers of processed tomato products strongly preferred attributes such as Country of origin, Organic, and Social and economic sustainability labels. In addition, the analysis shows the existence of three distinct consumer segments such as “traditional,” “price-sensitive,” and “sustainable” consumers. The largest one was price-sensitive consumers followed by sustainable and traditional ones. Discussion Our findings have practical implications for producers and policymakers. Producers may use claims about the product’s origin jointly with an organic production logo and ethical label to differentiate their products and raise revenues. Likewise, policymakers should enhance monitoring and control measures to ensure with environmental, social, and economic sustainable standards compliance. This will support building consumer trust for those credence attributes. Overall, this study adds valuable insights to the existing literature on consumer preferences for processed tomato products, providing results with high external validity using a large convenience sample.